Avaliação do desempenho térmico de forros produzidos com adição de resíduo EVA - Macedo, Jefferson Thiago (2020)
The footwear sector generates a huge volume of residues, among them ethylene vinyl acetate (EVA) with potential for use in prefabricated components for civil construction, such as false ceiling boards. This work verified the effectiveness of inserting the EVA residue in the production of plasterboard for the execution of false ceilings in houses of popular standard. The methodology was divided into three stages: the definition of the composite (plaster modified with EVA) with lower thermal conductivity, the production of the boards in real size and, finally, the installation of these as a ceiling in a full-scale prototype, in which monthly records (with data loggers) of temperature and humidity were performed, in periods characteristic of the local climate: rainy (winter) and dry (summer). The data were also compared with records made in similar environments with and without common plaster lining installed. The results showed that the plaster boards modified with EVA had a similar or better performance, according to the period analyzed,with regard to thermal insulation (reduction up to 1.8 ºC), when compared to the ordinary plaster ceiling. The study concluded that plasterboard modified with EVA has the potential to be used as false ceilings.